2011
DOI: 10.1152/jn.00186.2010
|View full text |Cite
|
Sign up to set email alerts
|

Partial Disinhibition Is Required for Transition of Stimulus-Induced Sharp Wave–Ripple Complexes Into Recurrent Epileptiform Discharges in Rat Hippocampal Slices

Abstract: Sharp wave-ripple complexes (SPW-Rs) in the intact rodent hippocampus are characterized by slow field potential transients superimposed by close to 200-Hz ripple oscillations. Similar events have been recorded in hippocampal slices where SPW-Rs occur spontaneously or can be induced by repeated application of high-frequency stimulation, a standard protocol for induction of long-lasting long-term potentiation. Such stimulation is reminiscent of protocols used to induce kindling epilepsy and ripple oscillations m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 84 publications
1
47
0
Order By: Relevance
“…Consistent with these observations of the interaction between manipulations that alter excitability, induction of recurrent epileptiform burst discharges by tetanic stimulation makes it more diffi cult to induce seizure-like activity using elevated K + [ 59 ]. Barbarosie and Avoli [ 7 ] observed that in the presence of the convulsant 4AP, seizure activity could be initiated following transection between CA1 and entorhinal cortex.…”
Section: Interictal Activity and Seizuresmentioning
confidence: 65%
“…Consistent with these observations of the interaction between manipulations that alter excitability, induction of recurrent epileptiform burst discharges by tetanic stimulation makes it more diffi cult to induce seizure-like activity using elevated K + [ 59 ]. Barbarosie and Avoli [ 7 ] observed that in the presence of the convulsant 4AP, seizure activity could be initiated following transection between CA1 and entorhinal cortex.…”
Section: Interictal Activity and Seizuresmentioning
confidence: 65%
“…ACh binds to both ionotropic nicotinic receptors, and metabotropic G protein-dependent muscarinic receptors. Nicotinic receptors containing a4 subunits found on hippocampal pyramidal cells show rapid desensitization (Liotta et al, 2011), while nicotinic receptors containing a7 subunits are typically expressed on parvalbumin-negative basket cells (Freund and Gulya´s, 1997). Muscarinic receptors, on the other hand, are present in different types of neurons and can be blocked by atropine, and, in case of M1 receptors, by pirenzepine (Mu¨ller and Misgeld, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…One model of seizure induction relies on increasing extracellular potassium concentrations. But rather than being pro-epileptic, the threshold for seizure induction is higher in slices in which SPW-Rs have been induced compared to naïve slices (Liotta et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…In the initial experiments we did not block GABAergic potentials. We therefore performed a series of experiments where we applied 5 mM bicuculline after CA3 removal which was previously shown to block phasic inhibition under our experimental conditions (Liotta et al, 2011). These results are depicted in Fig.…”
Section: Serotonin Affects Presynaptic Functionmentioning
confidence: 93%